Atomic Power - Taylor, Denis (Zede Journal of Ethiopian Engineers and Architects, 2023)
Dr. Taylor was formerly Chief UNESCO Advisor at the University College, Nairobi, Kenya and is now Professor of Electrical Engineering in the University of Strachlyde, Scotland. He is a leading scientist in the electronics field. He was among the British scientists who developed radar during the second World War. He has also headed the Plessey group of companis for a long time